PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROLE PLAYING PADA MATERI TATA SURYA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS VII MTs N 1 PADANGSIDIMPUAN - Fitri Armala; Muhammad Syafi'i; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to describe students' conceptual understanding and determine the improvement of students' conceptual understanding by applying a role playing type of cooperative learning model. The type of research used is Quasi Experimental, with a Nonequivalent Control Group Design. The subjects of this study were students of class VII MTs N 1 Padangsidimpuan, which consisted of 60 students and was divided into two classes, namely the experimental class and the control class. The data in this study were in the form of students' concept understanding scores after learning science by applying a role playing type cooperative learning model which was analyzed descriptively. Furthermore, the increase in understanding of the concept was analyzed using the SPSS Version 25 application for inferential analysis. Based on descriptive analysis and inferential analysis of data, it was found that the increase in students' conceptual understanding in the experimental class was in the good category with concept understanding in the good category with a posttest score of 73.05, while the control class was in the sufficient category, which was 58.17. Thus, it can be concluded that the application of the role playing type of cooperative learning model can improve students' conceptual understanding at MTs N 1 Padangsidimpuan.Key words : Learning Model, Role Playing, Concept Understanding